2001
DOI: 10.1055/s-2001-14284
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma Arising in Congenital Lung Cysts

Abstract: We report on a patient presenting with a bronchioloalveolar carcinoma fortuitously detected in the wall of a bronchogenic cyst. Evidence suggests that unstable epithelial cells contained within the cyst wall may lead to premalignant proliferation and neoplasia. In the current case, we demonstrated an increased proliferative activity in some areas of the cyst consistent with atypical adenomatous hyperplasia. Hence, we stress the importance of close follow-up of all suspected congenital lung cysts because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…The overwhelming majority of BACs are not associated with congenital lung cysts; the average age at diagnosis of all BACs is 68 years. 72 Twenty-one cases of BAC have been reported in patients with CPAM type 1; 24,50,[73][74][75][76][77][78][79][80][81][82][83][84] in this group the median diagnosis age is 18 years (range 6 months to 75 years) ( Table 2). In most of these cases, the BAC was an incidental finding in a cyst resected for other reasons.…”
Section: Bronchioloalveolar Carcinoma (Bac)mentioning
confidence: 99%
“…The overwhelming majority of BACs are not associated with congenital lung cysts; the average age at diagnosis of all BACs is 68 years. 72 Twenty-one cases of BAC have been reported in patients with CPAM type 1; 24,50,[73][74][75][76][77][78][79][80][81][82][83][84] in this group the median diagnosis age is 18 years (range 6 months to 75 years) ( Table 2). In most of these cases, the BAC was an incidental finding in a cyst resected for other reasons.…”
Section: Bronchioloalveolar Carcinoma (Bac)mentioning
confidence: 99%
“…16) However, multiple studies have shown that foregut cysts (including bronchogenic cyst and esophageal cyst) in old patients may become malignant. 17) Furthermore, with the growth of bronchogenic cyst, most patients may have complications, 11) which results in complicated disease conditions and surgical difficulties. Therefore, in principle, surgical resection should be applied as early as possible for the patients even without clinical symptoms.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Complications may occur, including infection, emoptysis, trachea or superior vena cava compression, intracystic haemorrhage, rupture, bronchial fistula, pneumothorax, and malignant changes, which have all been reported [9-13]. For this reason once the diagnosis of MBC is done, even if asymptomatic, surgical resection may be recommended.…”
Section: Discussionmentioning
confidence: 99%